Water treatment residual and vegetative filter strip effects on phosphorus transport dynamics - Green, Colleen Heather, author (Colorado State University. Libraries, 2004)
Agricultural practices are regarded as being sources of water and soil contamination. As a result, attention has been directed to management techniques of agricultural waste to minimize environmental impacts. Phosphorus (P) is recognized as a contaminant that causes adverse conditions in surface water bodies. Alum is a coagulant that municipalities use in the water treatment process to remove turbidity, color, taste, and odor from raw water while augmenting sedimentation rates. Water treatment residuals (WTRs) are the waste material from water treatment facilities. They generally consist of sand, silt, clay, organic substances, and coagulated aluminum compounds. Previous research has found that WTRs directly added to soil lessened the threat of non-point source pollution due to reduction in available P. Sorption isotherms indicated the WTR P partitioning coefficient is 185 L kg-1 versus 27 L kg-1 for the unnamed Aridic Argiustoll soil. These results indicate that WTR application may be used beneficially as a best management practice to control P availability. Experiments were conducted to determine i) if a WTR application rate for maximum P sorption could be identified, ii) if WTR applied to the soil surface would retain more P and leach less P than the soil alone, iii) if HYDRUS-1D model could predict total soil and WTR P transport, iv) if electron microprobe analysis using wavelength dispersive spectroscopy (EMPA-WDS) would identify Al-P complexes differently for various P concentrations, and v) if the Opus2Z model could elucidate how vegetative filter strips (VFSs) and WTRs impact TP transport in the interaction of surface water and soil water. A greenhouse experiment's MRP concentrations and Opus2Z model simulations indicated that a continuous layer of WTR over the soil with a depth of at least 5-6 mm was found to significantly reduce TP surface transport. Column experiments demonstrated that TP was mostly retained in the region of the WTR; this result was verified by the HYDRUS-1D model. The EMPA-WDS images illustrated P predominantly sorbed to the perimeter of a particle while P permeated the particle's interior as well as the interior at high P concentrations.
Keywords: soil sciences